Personal protective equipment related skin reactions in healthcare professionals during COVID‐19. Issue 3 (28th January 2021) - Abiakam, Nkemjika; Worsley, Peter; Jayabal, Hemalatha; Mitchell, Kay; Jones, Michaela; Fletcher, Jacqui; Spratt, Fran; Bader, Dan
Abstract: Since the outbreak of COVID‐19 pandemic, clinicians have had to use personal protective equipment (PPE) for prolonged periods. This has been associated with detrimental effects, especially in relation to the skin health. The present study describes a comprehensive survey of healthcare workers (HCWs) to describe their experiences using PPE in managing COVID‐19 patients, with a particular focus on adverse skin reactions. A 24‐hour prevalence study and multi‐centre prospective survey were designed to capture the impact of PPE on skin health of hospital staff. Questionnaires incorporated demographics of participants, PPE type, usage time, and removal frequency. Participants reported the nature and location of any corresponding adverse skin reactions. The prevalence study included all staff in intensive care from a single centre, while the prospective study used a convenience sample of staff from three acute care providers in the United Kingdom. A total of 108 staff were recruited into the prevalence study, while 307 HCWs from a variety of professional backgrounds and demographics participated in the prospective study. Various skin adverse reactions were reported for the prevalence study, with the bridge of the nose (69%) and ears (30%) being the most affected. Of the six adverse skin reactions recorded for the prospective study, the most common were redness blanching (33%), itchiness (22%), and pressure damage (12%). These occurred predominantly at the bridge of the nose and the ears. There were significant associations ( P < .05) between the adverse skin reactions with both the average daily time of PPE usage and the frequency of PPE relief. The comprehensive study revealed that the use of PPE leads to an array of skin reactions at various facial locations of HCWs. Improvements in guidelines are required for PPE usage to protect skin health. In addition, modifications to PPE designs are required to accommodate a range of face shapes and appropriate materials to improve device safety.